THE EFFECT OF INFRA RED THERAPY ON REDUCING HYPERTENSION - Untari, Ida; Prasojo, Ipin; Sarifah, Siti (Prosiding University Research Colloquium, 2024)
Hypertension is a silent killer disease that is still high internationally and nationally. One way to treat hypertension is providing infrared therapy. The aim of this study was to analyze the effect of infrared therapy on reducing hypertension. The research method is pre-experimental in one group. The population is elderly people who experience hypertension using purposive sampling technique. The intervention consisted of providing infra-red therapy 3 times a week for 2 weeks with a duration of 15 minutes. The blood pressure measurement instrument uses a digital blood pressure monitor and recording sheet. Blood pressure was recorded before and after each therapy and the average decrease in both systole and diastole was calculated. Next, an analysis of the effect of infrared therapy on reducing hypertension was carried out at a significant 5% with the result that infrared therapy was able to reduce hypertension (p: 0.025).